Status and prospects in stellarator research at IPP KIPT - Moiseenko, V.E.; Kovtun, Yu.V.; Garkusha, I.E. (Вопросы атомной науки и техники, 2021)
A review of works performed at the Stellarator Department of KIPT is presented. It includes radio frequency (RF) plasma start-up, RF wall conditioning, RF plasma heating and diagnostics improvements at Uragan stellarators, studies of discharges for wall conditioning at Wendelstein 7-X Helias and some theoretical studies on magnetic configurations and tritium breeding. The prospects for the studies are associated with deeper involvement in EUROfusion activities.